Role of waqf for elderly care to improve employee retention strategies: a qualitative study / Nurul Asyiqin Abdul Fatah … [et al.] - Abdul Fatah, Nurul Asyiqin; Ismail, Shafinar; Kamarudin, Nur Asyikeen; Ahmad, Ismail; Hamzah, Fazlinda (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study examined the relationship between work-life balance and employee retention in Malaysia. Employee retention strategies are crucial in building capacity towards sustainable social and economic growth. Hence, the issue of work-life balance is an eye-opener to the public because it can affect the employees and their surroundings. This is because there are many children nowadays who neglect their parents due to work commitments and pressure to cope with the financial burden. Therefore, this study investigated the capacity of waqf funding in order to resolve this issue. This study employed interviews in order to get the expert’s point of view particularly from the elderly care centres and non-government associations. The purposive sampling procedure was adopted in this study. The findings indicate that waqf can help to increase wellbeing and facilitate better employee retention strategies. The findings achieved in this research will be of interest to practitioners and academicians who are concerned with the retention strategies at the workplace in order to support employees to be retained in their current organisations.